Interleukin-10 Attenuates Hypochlorous Acid-Mediated Cytotoxicity to HEI-OC1 Cochlear Cells - Mwangi, Martin; Kil, Sung-Hee; Phak, David; Park, Hun Yi; Lim, David J.; Park, Raekil; Moon, Sung K. (Frontiers in Cellular Neuroscience, 2017)
Inflammatory reaction plays a crucial role in the pathophysiology of acquired hearing loss such as ototoxicity and labyrinthitis. In our earlier work, we showed the pivotal role of otic fibrocytes in cochlear inflammation and the critical involvement of proinflammatory cytokines in cisplatin ototoxicity. We also demonstrated that otic fibrocytes inhibit monocyte chemoattractant protein 1 (CCL2) upregulation in response to interleukin-10 (IL-10) via heme oxygenase 1 (HMOX1) signaling, resulting in suppression of cochlear inflammation. However, it is still unclear how IL-10 affects inflammation-mediated cochlear injury. Here we aim to determine how hypochlorous acid, a model inflammation mediator affects cochlear cell viability and how IL-10 affects hypochlorous acid-mediated cochlear cell injury. NaOCl, a sodium salt of hypochlorous acid (HOCl) was found to induce cytotoxicity of HEI-OC1 cells in a dose-dependent manner. Combination of hydrogen peroxide and myeloperoxidase augmented cisplatin cytotoxicity, and this synergism was inhibited by N-Acetyl-L-cysteine and ML-171. The rat spiral ligament cell line (RSL) appeared to upregulate the antioxidant response element (ARE) activities upon exposure to IL-10. RSL cells upregulated the expression of NRF2 (an ARE ligand) and NR0B2 in response to CoPP (a HMOX1 inducer), but not to ZnPP (a HMOX1 inhibitor). Adenovirus-mediated overexpression of NR0B2 was found to suppress CCL2 upregulation. IL-10-positive cells appeared in the mouse stria vascularis 1 day after intraperitoneal injection of lipopolysaccharide (LPS). Five days after injection, IL-10-positive cells were observed in the spiral ligament, spiral limbus, spiral ganglia, and suprastrial area, but not in the stria vascularis. IL-10R1 appeared to be expressed in the mouse organ of Corti as well as HEI-OC1 cells. HEI-OC1 cells upregulated Bcl-xL expression in response to IL-10, and IL-10 was shown to attenuate NaOCl-induced cytotoxicity. In addition, HEI-OC1 cells upregulated IL-22RA upon exposure to cisplatin, and NaOCl cytotoxicity was inhibited by IL-22. Taken together, our findings suggest that hypochlorous acid is involved in cochlear injury and that IL-10 potentially reduces cochlear injury through not only inhibition of inflammation but also enhancement of cochlear cell viability. Further studies are needed to determine immunological characteristics of intracochlear IL-10-positive cells and elucidate molecular mechanisms involved in the otoprotective activity of IL-10.